1989
DOI: 10.1530/jrf.0.0870809
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on cytoskeletal organization and in-vivo survival after freezing of rabbit oocytes

Abstract: NBD-phallacidin revealed a polymerized actin distribution in the cortical region of the rabbit egg and along junctional feet. Staining with anti-alpha-tubulin antibody showed that the microtubule distribution was restricted to the barrel-shaped spindle. After cryoprotective treatment in the presence of propanediol, cortical polymerized actin was no longer visible within the egg and along junctional feet but filamentous actin was still present after treatment with dimethylsulphoxide. However, exposure to dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
5

Year Published

1990
1990
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 32 publications
2
50
0
5
Order By: Relevance
“…Additionally, the in vitro fertilization rate was similar for frozen and fresh oocytes (70% versus 81%). In other studies, there was successful cryopreservation of oocytes of several species, with live births reported for mice [36], rabbits [37], and cows [1]. The success obtained in these experiments may be due to the cryopreservation protocols being more appropriate for the developmental stage of the oocytes and the preservation forms used (oocytes without cumulus cells), as well as to intrinsic characteristics of each species.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, the in vitro fertilization rate was similar for frozen and fresh oocytes (70% versus 81%). In other studies, there was successful cryopreservation of oocytes of several species, with live births reported for mice [36], rabbits [37], and cows [1]. The success obtained in these experiments may be due to the cryopreservation protocols being more appropriate for the developmental stage of the oocytes and the preservation forms used (oocytes without cumulus cells), as well as to intrinsic characteristics of each species.…”
Section: Discussionmentioning
confidence: 90%
“…However, the success rate of human oocyte cryopreservation is still low. Achievement of a clinically feasible technique requires further research to better understand and overcome cryopreservationassociated stresses and problems such as spindle disorganization (1-3), disruption of cytoskeletal elements (3,4), and increased polyploidy (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using metaphase II (MII) human (10,11), mouse (1,12), cow (2), and rabbit (4) oocytes showed that cooling, cryoprotectants, or freezing and thawing cause depolymerization of the MII spindle microtubules with a consequence of chromosomal scattering. In addition, exposure of MII oocytes to cryoprotectants or a freeze-thaw cycle disrupts microfilament network and induces formation of several cytoplasmic microtubular asters or network (3,4). Although these alterations in microfilament and cytoplasmic microtubule organization of MII oocytes can be reversed by a subsequent incubation, changes in the spindle morphology are partially irreversible (3,4,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been demonstrated that the cryopreservation of oocytes originating from antral follicles is successful in mice (Carrol and Gosden, 1993), rabbits (Vicent et al, 1989) and bovine (Fuku et al, 1992), followed by IVF after thaw, resulting in the birth of normal offspring in all of these species. In domestic felines, Luvoni and Pellizzari (2000) demonstrated that the mature oocyte could be cryopreserved and, soon after, fertilized in vitro with success.…”
Section: Recovery Of Oocytes Included In Antral Folliclesmentioning
confidence: 99%